Ekspresi Protein Ki-67 pada Biopsi Kolonoskopi Adenoma dan Karsinoma Kolorektal - Ni Made Maharini Rahayu; Moestikaningsih .; Ketut Mulyadi (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2014)
Background Neoplastic lesion in colorectal could be adenoma and colorectal carcinoma (CRC). An invasion in muscularis mucosa is a criteria for colorectal carcinoma. Diagnosis is formed with histopatologic interpretation. In colorectal-biopsy preparation interpretation, determining limited invasion is sometimes difficult so that it needs other diagnostic tools. The aim of this study was to evaluating the difference of Ki-67 mean expression in colorectal adenoma and CRC. Methods This study was cross-sectional study on colorectal adenoma and CRC. Cases were diagnosed by colonoscopy-biopsy between 2011 and 2012. It did re-interpretation of HE preparation of adenoma or colorectal carcinoma diagnosis and determination of the degree of differentiation of those adenoma and colorectal carcinoma. Immunohistochemical Ki-67 staining was interpreted with light microscope. The percentage of the stained tumour cells was counted. The difference of mean in Ki-67 expression of colorectal adenoma and CRC was analyzed with t-test with significance level at p